Water, wastewater, and stormwater infrastructure management - Grigg, Neil S. (Boca Raton, Fla. : CRC Press, 2012)
"The second edition of a bestseller, this book discusses details the latest research on management practices for water and sewer capital facilities with an emphasis on infrastructure. It explores recent advances and highlights the technique asset management, which has received international acceptance and applies across various infrastructure sectors. It covers the components of asset management systems, including computer platforms and software packages, methods for condition assessment and ratings, risk-based decision support systems, decision making protocols, triple bottom line business cases, and new options for repair, rehabilitation, and replacement of buried pipe assets"--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Municipal engineering; Municipal water supply; Sewerage; Infrastructure (Economics) -- Management; Electronic books